Homoeopathic Treatment in Hypothyroidism—An Open-Label, Prospective, Single-Arm, Clinical Trial - Ray, Aniket Singha; Ganguly, Subhasish; Mukherjee, Shyamal Kumar; Hazra, Pallavi; Dutta, Souvik; Nath, Arunava; Koley, Munmun; Saha, Subhranil (Homœopathic Links, 2021)
Background Hypothyroidism is one of the most common endocrinal disorders in India and its incidence is gradually increasing. A preliminary clinical trial was conducted to assess the probable role of individualised homoeopathic (IH) medicines in hypothyroidism with the assessment of hormonal titre (serum thyroid-stimulating hormone [TSH] and free T4) and symptomatic improvement.Methods An open-label, prospective, single-arm trial was conducted on 40 patients suffering from hypothyroidism at the outpatient of D. N. De Homeopathic Medical College and Hospital, West Bengal, India, and treated with IH. Serum TSH and FT4 were considered as the primary outcomes and Zuleswki's clinical scoring (ZCS) and thyroid symptom questionnaire (TSQ) as the secondary outcomes, measured at baseline and after 3 months of treatment. Intention-to-treat sample was analysed in the end by paired t-tests.Results Total 58 patients were screened, of which 40 patients were enrolled; 4 patients dropped out, 36 patients completed the trial. Mean age was 44 years (standard deviation: 13.6), and majority of the patients were female (87.5%). Improvement in both primary and secondary outcomes was statistically significant (p <0.001, paired t-tests), TSH (mean reduction: 2.7, 95% confidence interval [CI]: 1.9–3.6, p = 0.001), FT4 (mean increase: −0.2, 95% CI: −0.3 to −0.2, p = 0.001), ZCS (mean reduction: 3.7, 95% CI: 2.9–4.6, p = 0.001), and TSQ (mean reduction: 2.9, 95% CI: 2.1–3.6, p = 0.001). Most frequently used medicines were Sulphur (20%), Pulsatilla nigricans (12.5%), Iodium (10%), Phosphorus (10%), and Natrum muriaticum (7.5%).Conclusion This study showed promising treatment effects of IH in hypothyroidism. Randomised trials are warranted (Trial registration: CTRI/2018/11/016451; UTN: U1111–1223–2292).
Keywords: clinical trial; homoeopathy; hypothyroidism; TSH; free T4